2020
DOI: 10.3389/fendo.2020.592495
|View full text |Cite
|
Sign up to set email alerts
|

High BMI and Insulin Resistance Are Risk Factors for Spontaneous Abortion in Patients With Polycystic Ovary Syndrome Undergoing Assisted Reproductive Treatment: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe risk of spontaneous abortion in patients with polycystic ovary syndrome (PCOS) undergoing assisted reproductive treatment (ART) is higher than that in patients without PCOS, however, no definitive risk factors have been confirmed to associate with the high spontaneous abortion rate in PCOS patients undergoing ART. This study was performed to assess the impact of relevant risk factors on spontaneous abortion in patients with PCOS. Clinical questions were formulated and organized according to the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 91 publications
2
35
1
1
Order By: Relevance
“…However, this was not found in our study. A recent systematic review and meta-analysis also showed that HA does not increase the risk of abortion in patients with PCOS 18 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this was not found in our study. A recent systematic review and meta-analysis also showed that HA does not increase the risk of abortion in patients with PCOS 18 .…”
Section: Discussionmentioning
confidence: 96%
“…Abortion is a common complication of pregnancy. The aetiology of abortion is complex: obesity 17 , insulin resistance 18 , hyperandrogenism 19 , the quality of oocytes and endometrial abnormalities might be associated with the occurrence of abortion [20][21][22] . As reported in prior studies, women with PCOS are associated with an increased risk of abortion 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options comprise dietary modification or medications, both of which improve insulin sensitivity [37,38]. It can be added that insulin resistance increases the risk of spontaneous abortion after assisted reproduction technology treatment [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial hyperplasia is prone to occur under the stimulation of estrogen and insulin for a long time, leading to a significant decrease in pregnancy rate of PCOS patients. [ 6 , 7 ] So, improving insulin resistance is very necessary for PCOS women. The mechanisms of insulin resistance are very complex, they are usually related to obesity, metabolic abnormalities, gene expression and so on.…”
Section: Introductionmentioning
confidence: 99%